2013
DOI: 10.1007/s00595-013-0695-1
|View full text |Cite
|
Sign up to set email alerts
|

Short-term intravenous antimicrobial prophylaxis for elective rectal cancer surgery: results of a prospective randomized non-inferiority trial

Abstract: PurposeTo investigate the non-inferiority of postoperative single-dose intravenous antimicrobial prophylaxis to multiple-dose intravenous antimicrobial prophylaxis in terms of the incidence of surgical site infections (SSIs) in patients undergoing elective rectal cancer surgery by a prospective randomized study.MethodsPatients undergoing elective surgery for rectal cancer were randomized to receive a single intravenous injection of flomoxef (group 1) or five additional doses (group 2) of flomoxef after the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The usefulness of extended antibiotic prophylaxis in the immediate postoperative period in TPE remains limited. Koh et al [27] suggest that prolonged courses of antibiotic administration in PE may reduce septic complications, which is in contrast to the findings of Ishibashi et al [28] on patients undergoing surgery for rectal cancer; the authors did not observe a significant reduction in SSI incidence among patients receiving a single dose of postoperative antibiotics vs. multiple-dose antibiotics. Other authors argue that prolonged courses of antibiotic prophylaxis may cause the risk of increasing microbial resistance infections [29,30].…”
Section: Discussionmentioning
confidence: 80%
“…The usefulness of extended antibiotic prophylaxis in the immediate postoperative period in TPE remains limited. Koh et al [27] suggest that prolonged courses of antibiotic administration in PE may reduce septic complications, which is in contrast to the findings of Ishibashi et al [28] on patients undergoing surgery for rectal cancer; the authors did not observe a significant reduction in SSI incidence among patients receiving a single dose of postoperative antibiotics vs. multiple-dose antibiotics. Other authors argue that prolonged courses of antibiotic prophylaxis may cause the risk of increasing microbial resistance infections [29,30].…”
Section: Discussionmentioning
confidence: 80%
“…(Southwood, 2014) No difference in infection rate in human patients undergoing clean, clean-contaminated or contaminated procedures was appreciated with a single dose at time of surgery versus prolonged antimicrobial administration. (Aberg & Thore, 1991;Bansal et al, 2012;Bidkar et al, 2013;Esposito, 1999;Fernandez et al, 2001;Ishibashi et al, 2014;Schein et al, 1994;Sharma et al, 2010) Furthermore, small animal patients receiving post-operative antimicrobial drugs actually had a higher reported infection rate than patients receiving no antimicrobials (8.2% vs. 4.3%). (Conzemius et al, 1997) Although prolonged prophylactic usage has been justified previously for equine synovial endoscopy TA B L E 2 Summary data of final categorical variables used to model the risk of post-operative GI complications in elective equine endoscopic surgeries (2014)(2015)(2016)(2017)(2018)496 The total numbers in each level of patient sex, antibiotic used, attending faculty (anonymized) and breed that had a recorded GI related complication (yes or no) as well as the percentage within each level that had a complication are shown.…”
Section: Discussionmentioning
confidence: 99%
“…Human patients undergoing elective surgery for rectal cancer receiving a single i.v. dose of a third‐generation cephalosporin had a surgical site infection rate that was not different to that of patients receive 5 additional doses after surgery when preoperative mechanical and chemical bowel preparations were used (13.7 vs. 13.6%, respectively) . There was no difference in wound infection rate or graft success rate in patients undergoing tympanomastoid surgery treated with antimicrobials perioperatively only compared with an additional 8 days post operatively .…”
Section: National Research Council Operative Wound Classificationmentioning
confidence: 92%
“…Surgical site infection rates have been compared in human patients undergoing various clean‐contaminated or contaminated procedures. With all of these studies, there has been no difference in infection rates with short duration prophylaxis (typically a single dose at the time of surgery) vs. a more prolonged duration (at the time of surgery followed by multiple doses post operatively) and, in fact, several studies showed no benefit to prophylactic antimicrobial drug use at all . Human patients undergoing elective surgery for rectal cancer receiving a single i.v.…”
Section: National Research Council Operative Wound Classificationmentioning
confidence: 99%